INFLUENCE OF LEADERSHIP COMPETENCY ON COMPLETION OF ROAD CONSTRUCTION PROJECTS IN NASARAWA STATE, NIGERIA. - Daniel, Bahago Markus; Paul, Dr. Samson Nyang'au (Human Resource and Leadership Journal, 2019)
Purpose: The study assessed the influence of leadership competency on completion of road construction projects in Nasarawa State, Nigeria. The study sought to finding out the influence of adequate knowledge and completion of road construction projects in Nasarawa State, Nigeria. The study was seeking to find out the influence of leadership skills on completion of road construction projects in Nasarawa State, Nigeria. Methodology: The collection of primary data was from direct responses from Nasarawa State government top management through the use of structured questionnaire. The collected data was analyzed through Statistical Package for Social Sciences version 22. Descriptive and inferential statistics were used in analyzing data where multiple regression analysis was used to examine the influence of independent variables on the dependent variable. Results: The study found out that indeed leadership competencies have a statistical significant influence on completion of road construction projects since the P value was 0.000 which is positive of significant rate of respondents.